Efektivitas Kontrak Lump Sum pada Proyek Konstruksi di Kabupaten Kutai Barat - Sopiani Sopiani; Findia Findia; Habir Habir (LPPM Institut Pendidikan Nusantara Global, 2026)
Lump sum contracts are widely used in Indonesian construction, yet questions persist about which factors—cost effectiveness, schedule effectiveness, or risk management—most significantly influence work quality and contractor satisfaction. This research addresses two critical questions: (1) what factors affect lump sum contract effectiveness based on project performance, and (2) which of the three variables most significantly impact work quality and contractor satisfaction in West Kutai District projects. The study employed quantitative methods with 30 contractor respondents, collecting data through structured 5-point Likert scale questionnaires. Validity was tested using Pearson correlation analysis and reliability assessed via Cronbach's Alpha. Multiple linear regression examined the influence of the three independent variables on work quality and contractor satisfaction. Results indicate that cost effectiveness significantly affects contractor satisfaction (β = 0.337; t = 2.097; p = 0.046), while schedule effectiveness and risk management show no significant effects on either dependent variable. The regression models explain only 41.6% of contractor satisfaction variance and 22.4% of work quality variance, indicating substantial unexplained factors. These findings demonstrate that among examined variables, cost effectiveness is the primary determinant of contractor satisfaction in lump sum contracts. However, the incomplete variance explanation emphasizes that identifying additional factors influencing contract effectiveness is essential for improving construction project outcomes in regional contexts